PENERAPAN METODE QUALITY FUNCTION DEPLOYMENT (QFD) DALAM UPAYA PENINGKATAN KUALITAS PRODUK INDUSTRI RUMAHAN ROTI RAJA ASIH - Raharja, Firman; Kusumawardhani, Amie (Diponegoro Journal of Management, 2017)
Raja Asih Home Industry is one of the SMEs engaged in cakes and bakery in Cirebon regency. In the future, the bakery market will increase, so there will be a lot of business in the field of cakes and bakery, making the competition increasingly tight. One way to win the competition is by continuously improving the quality of the product to suit the consumer's wishes. This study discusses the application of Quality Function Deployment method, which aims to ensure that the products produced can meet the level of quality desired by consumers. Application of QFD method in improving product quality using House of Quality matrix (HoQ).The data in this study was collected by survey method using structured and situational interviews as well as questionnaires on 50 respondents. The method used is Quality Function Deployment Method (QFD).The result of this research is that there are 6 factors from bakery product that is considered very important by consumers, they are: texture, color of maturity, shape and size, bread quality, nutritional composition information and expiration time and company reputation. Based on the calculation of technical interest, which need to be prioritized in the improvement by the company are: selection of raw materials, cleaning equipment, machine maintenance and selection of jam.